2017
DOI: 10.22456/1679-9216.80637
|View full text |Cite
|
Sign up to set email alerts
|

Virulence Factors in Staphylococcus aureus and Quality of Raw Milk from Dairy Cows in a Semiarid Region of Northeastern Brazil

Abstract: Background: Milk quality is considered unsatisfactory in Brazil due to factors of a social, economic, cultural, and climatic nature. Mastitis is the main disease that affects dairy herds. Microorganisms of the genus Staphylococcus are the most frequently isolated pathogens in cases of mastitis in bovines. Staphylococcus aureus requires more attention because they have the ability to develop resistance to antimicrobials used in the treatment of mastitis. Thus, the aim of the present study was to evaluate virule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…or even for other genera of medical importance. Additionally, despite the direct comparison of the results of the present study with others also conducted in Brazil is not possible, due to the difference in the distribution of the isolates (geographical and temporal) and different methodologies used to assess virulence factors and resistance genes; other studies performed in S. aureus from different Brazilian states also point to the importance of biofilm production and presence of enterotoxins and antimicrobial resistance genes (blaZ) for the pathogenesis of mastitis, besides the potential food poisoning risk associated with dairy products [5][6][7].…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…or even for other genera of medical importance. Additionally, despite the direct comparison of the results of the present study with others also conducted in Brazil is not possible, due to the difference in the distribution of the isolates (geographical and temporal) and different methodologies used to assess virulence factors and resistance genes; other studies performed in S. aureus from different Brazilian states also point to the importance of biofilm production and presence of enterotoxins and antimicrobial resistance genes (blaZ) for the pathogenesis of mastitis, besides the potential food poisoning risk associated with dairy products [5][6][7].…”
Section: Discussionmentioning
confidence: 45%
“…Indeed, studies conducted in countries from Europe, Africa, and America have reported a high prevalence of S. aureus in dairy cows reaching 41% in France (1995-2012), 47.2% in herds from Italy (2012-2013) [2], 74% in Ethiopia (2014-2015) [3], and Canada (2003)(2004)(2005) [4]. In Brazil, several studies have showed the importance of S. aureus in the epidemiology of mastitis in cattle [5][6][7][8]. Although it can be involved in clinical mastitis (especially after calving), the infection is usually subclinical, causing no visible changes in milk or udder [1].…”
Section: Introductionmentioning
confidence: 99%
“…The high prevalence of S . aureus in this study (16.72%) might be linked to conventional hand milking, the lack of regular post-milking teat dip, dairy owners’ lack of knowledge about dry cow therapy, and operating procedures along the milk production chains [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The variations in the load of S . aureus between towns might be due to the differences in handling practices, sanitary conditions, and operating procedures along the milk production chain [ 34 , 36 ]. However, the total log10CFU/ml mean count of S .…”
Section: Discussionmentioning
confidence: 99%
“…The microbial cell populations after GMM treatment were measured by the plate count method according to a previous study (42). The pathogen cells were collected as described above and resuspended to a final cell concentration of approximate 10 5 CFU/mL (OD 600 ≈ 0.05) with sterile broth.…”
Section: Methodsmentioning
confidence: 99%